Prototipe Sistem Gate Otomatis pada Bendungan PLTA - Sukma Abadi; Yiyin Klistafani; Sitti Nurlatifa; Jeri Christanto (Jurnal Sinergi Jurusan Teknik Mesin, 2023)
This study aims to make a prototype mechanism for opening and closing the gate on a hydropower dam using the Arduino Uno microcontroller. The research was conducted by making two gates (gate-1 and gate-2) which will open or close based on the water level of the dam. Gate-1 and gate-2 will close if the water level of the dam does not exceed the limit for immediate reduction. The test was carried out with variations in the conditions of water entering the dam, namely calm water conditions, heavy water conditions, and low water conditions. From the tests carried out, it was found that gate-1 always opens when the water level reaches 8 cm or more, while gate-2 opens when the water level starts to reach 11 cm. The length of time gate-1 and gate-2 open according to the water level of the dam.